Effects of Randomized Controlled Infancy-Onset Dietary Intervention on Leukocyte Telomere Length - The Special Turku Coronary Risk Factor Intervention Project (STRIP) - Pitkanen Niina; Pahkala Katja; Rovio Suvi P; Saijonmaa Outi J; Nyman Anna E; Jula Antti; Lagström Hanna; Viikari Jorma S A; Rönnemaa Tapani; Niinikoski Harri; Simell Olli; Fyhrquist Frej; et al. (MDPI, 2022)
Reduced telomere length (TL) is a biological marker of aging. A high inter-individual variation in TL exists already in childhood, which is partly explained by genetics, but also by lifestyle factors. We examined the influence of a 20-year dietary/lifestyle intervention on TL attrition from childhood to early adulthood. The study comprised participants of the longitudinal randomized Special Turku Coronary Risk Factor Intervention Project (STRIP) conducted between 1990 and 2011. Healthy 7-month-old children were randomized to the intervention group (n = 540) receiving dietary counseling mainly focused on dietary fat quality and to the control group (n = 522). Leukocyte TL was measured using the Southern blot method from whole blood samples collected twice: at a mean age of 7.5 and 19.8 years (n = 232; intervention n = 108, control n = 124). Yearly TL attrition rate was calculated. The participants of the intervention group had slower yearly TL attrition rate compared to the controls (intervention: mean = -7.5 bp/year, SD = 24.4 vs. control: mean = -15.0 bp/year, SD = 30.3; age, sex and baseline TL adjusted beta = 0.007, SE = 0.004, p = 0.040). The result became stronger after additional adjustments for dietary fat quality and fiber intake, serum lipid and insulin concentrations, systolic blood pressure, physical activity and smoking (beta = 0.013, SE = 0.005, p = 0.009). A long-term intervention focused mainly on dietary fat quality may affect the yearly TL attrition rate in healthy children/adolescents.